Murabahah Financing in Practice: An Analytical Study at Sharia Bank, Sungai Penuh Branch - Iswari, Tiya; Sarmigi, Elex; Al Biruni, Abdurrahman; Aunurrochim Mas'ad, Muhammad (Journal of Islamic Economics Perspectives, 2024)
This study examines the implementation of murabahah financing at the Sungai Penuh branch of Islamic Bank. Murabahah is one of the most dominant Islamic banking products in Indonesia, contributing 57.16% of total Islamic bank financing. This study analyzes the characteristics of the murabahah products offered, the procedures for implementing the murabahah contract, the mechanism for ensuring sharia compliance, risk management strategies, and the positive impact of murabahah financing on the economy and customer welfare. Sungai Penuh City is a potential area for the development of Islamic banking because the majority of its population is Muslim. The method used in this study is qualitative with a descriptive approach. The types of data used in this study are primary data and secondary data with data collection techniques by means of observation, interviews and documentation. The data obtained in the field are then analyzed by data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of murabahah financing in Sungai Penuh is generally in accordance with sharia principles and in accordance with the provisions of the DSN-MUI Fatwa and the Islamic Banking Law. However, there are still some challenges such as pricing, risk management, and sharia compliance. Suggesting that Islamic banks should improve customer understanding and develop innovative murabahah products to further strengthen the growth of Islamic banking in the Sungai Penuh area.